2016
DOI: 10.1016/j.jaad.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

The study of nevi in children: Principles learned and implications for melanoma diagnosis

Abstract: Melanocytic nevi are a strong phenotypic marker of cutaneous melanoma risk. Changes in nevi during childhood and adolescence make these prime periods for studying nevogenesis. Insights gained by the study of nevi in childhood have implications for melanoma detection in both adults and children. A more comprehensive understanding of the morphologic characteristics of nevi in different anatomic locations, in association with the patient’s age and pigmentary phenotype may aid in the identification of melanomas. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 72 publications
2
18
0
3
Order By: Relevance
“…These patients also presented with lesions that exhibited more frequently signs of atypia such as mitoses, high lymphocytic infiltrate and cellular atypia but these differences were not found to be statistically significant. The characteristics of lesions compared to total naevus count and age group were not investigated, as total naevus count for patients <20 may change with increasing age …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients also presented with lesions that exhibited more frequently signs of atypia such as mitoses, high lymphocytic infiltrate and cellular atypia but these differences were not found to be statistically significant. The characteristics of lesions compared to total naevus count and age group were not investigated, as total naevus count for patients <20 may change with increasing age …”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of lesions compared to total naevus count and age group were not investigated, as total naevus count for patients <20 may change with increasing age. 33,34 Interestingly, patients with SN belonging to the ≥40 years age group reported longer periods of annual sun exposure and more frequently a positive history for painful sunburn. These patients also more frequently reported never using any type of sunscreen before the appearance of the SN compared to the other age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral globular pattern is another dermoscopic pattern with an age‐dependent prevalence. The frequency of peripheral globules also decreases with aging .…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have reported that the first 2 decades of life are remarkable for appearance and growth of melanocytic nevi, so this period is important for studying nevogenesis . Nevus counts also increase during childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation